Preparation method of bimetal-MOF modified diaphragm for lithium-sulfur battery as well as product and application of bimetal-MOF modified diaphragm
By modifying the bimetal-MIL-101 series of materials on the lithium-sulfur battery separator, the problem of polysulfide shuttle effect in lithium-sulfur batteries is solved, and the cycle performance and rate performance of the battery are significantly improved, achieving more efficient electrochemical performance and lower production costs.
Patent Information
- Application Number
- CN202411974535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
Lithium-sulfur batteries have poor sulfur conductivity, low utilization rate, slow reaction kinetics and shuttle effects of polysulfides, resulting in rapid capacity decay and loss of active substances.
The separator is modified by bimetallic-MIL-101 series metal organic frame material. By coating the bimetallic-MIL-101 series materials on the surface of the battery separator, the dissolution and shuttle effect of polysulfides are inhibited, and lithium ion conductivity and electron conductivity are improved.
It effectively improves the circulation performance and rate performance of lithium-sulfur batteries, extends the service life of the battery, and reduces the cost and environmental impact of the battery.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of chemical power sources, and in particular to a preparation method of a bimetallic-MOF modified diaphragm for a lithium-sulfur battery, and a product and application thereof. Background Art
[0002] At present, the social demand for energy is constantly expanding, and my country's energy supply and demand are gradually becoming tight. With the increasing consumption of non-renewable energy, various greenhouse gases have caused great damage to the environment, and fossil energy is facing the risk of depletion. Energy and environmental issues need to be solved urgently. However, based on existing technology, lithium-ion batteries have the disadvantages of low capacity and short cycle life, which makes it difficult to meet the growing social needs.
[0003] With the upgrading of the electronics industry, high energy density energy storage systems have become increasingly critical. In particular, the rapid rise of modern electric vehicles has put forward extremely high requirements for battery energy density. Commercial lithium-ion batteries can no longer meet the application requirements of some electronic devices. As one of the core battery technologies in the post-lithium era, lithium-sulfur batteries have high energy density. Their theoretical energy density reaches 2600Wh·kg-1, which is 5 times that of commercial lithium batteries. In addition, they have abundant sulfur reserves, are environmentally friendly, and have low costs. They meet the requirements of electric vehicles for batteries, and also meet the requirements of electronic portable devices for batteries to be "light, small, and thin."
[0004] Lithium-sulfur battery is a secondary high-density energy battery system that uses metallic lithium as the negative electrode and elemental sulfur or sulfur-based composite materials as the positive electrode. The theoretical specific capacity of elemental sulfur can reach 1675mAh·g-1.
[0005] Although lithium-sulfur batteries have many advantages, they still face many challenges and difficulties, such as poor sulfur conductivity, low utilization, slow reaction kinetics, insulation of redox product lithium sulfide, dissolution of polysulfide ions and its "shuttle effect", stability of metal lithium negative electrode, etc. The most serious one is that polysulfides are generated during the discharge process, which are easy to dissolve and diffuse in the organic electrolyte, and react with the positive sulfur material and the negative lithium sheet to generate insulating precipitates (Li2S2 and Li2S), thereby destroying the negative electrode. On the other hand, it also causes the loss of active materials, resulting in rapid capacity decay of lithium-sulfur batteries and greatly reducing the utilization of active materials. Strategies to improve the performance of lithium-sulfur batteries have always attracted much attention. Successfully limiting the shuttle effect of polysulfides and promoting the redox reaction of sulfur have become the key to preparing high-performance lithium-sulfur batteries. If the battery structure characteristics of lithium-sulfur batteries can be used to design a diaphragm that can effectively block the shuttling of polysulfides, the capacity performance and cycle performance of lithium-sulfur batteries will be greatly improved.
[0006] In recent years, the academic community has conducted research from several aspects: (1) For sulfur cathode: prepare porous carbon materials to encapsulate sulfur to form carbon-sulfur composite materials, so that elemental sulfur is dispersed in the porous carbon materials to inhibit the dissolution of polysulfides in the electrolyte; (2) For electrolyte: add some additives to the electrolyte to optimize the composition of the electrolyte or use new electrolytes; (3) For lithium anode: modify and protect the metallic lithium negative electrode to organize the corrosion of the electrolyte and polysulfides on the lithium negative electrode; (4) For diaphragm: design a barrier layer to prevent the dissolution of polysulfides.
[0007] Functional modification of separators has been demonstrated to be a facile, low-cost, and successful technique to immobilize LiPSs and mitigate their diffusion. Commercial polypropylene (PP) separators serve as electrical isolation and ion transport mediators between the anode and cathode. However, the porous channels in PP separators are also unobstructed for Li-ion batteries, resulting in low sulfur utilization and unfavorable capacity fading. So far, various innovative materials have been explored as barrier coatings to immobilize LiPSs with nanostructured carbon materials through physical confinement and to immobilize polar materials such as metal oxides, sulfides, selenides, carbides, and nitrides through chemical adsorption. Summary of the invention
[0008] In view of the current problems of lithium-sulfur batteries, the present invention aims to provide a method for preparing a bimetallic-MOF modified diaphragm for lithium-sulfur batteries.
[0009] Another object of the present invention is to provide a bimetallic-MOF modified diaphragm product for lithium-sulfur batteries prepared by the above method.
[0010] Another object of the present invention is to provide an application of the above product.
[0011] The object of the present invention is achieved by the following scheme: A modified diaphragm for lithium-sulfur battery and a preparation method thereof, comprising the following steps: S1, adding bimetallic-MIL-101 series metal organic framework materials into NMP (N-methylpyrrolidone) to obtain a mixed solution; S2, adding the binder into NMP and mixing evenly to obtain a mixed solution; S3, S1 and S2 are mixed evenly in a fixed ratio to obtain a mixed solution as a coating slurry, and then the coating slurry is evenly coated on the surface of the battery separator and dried to obtain a bimetallic-MIL-101 modified separator.
[0012] On the basis of the above scheme, the bimetallic-MIL-101 series metal organic framework materials are one or more of MIL-101 (Ti-Al), MIL-101 (Ti-Ni), MIL-101 (Ti-Co), MIL-101, etc.
[0013] On the basis of the above scheme, in S3, the drying is vacuum drying at 60° C. for 12 hours, or natural air drying.
[0014] Based on the above solution, the battery separator is a PP separator or a PE separator including Celgard2400.
[0015] Based on the above solution, in S3, the coating layer thickness is 6 um.
[0016] The present invention provides a bimetallic-MOF modified diaphragm for a lithium-sulfur battery, which is prepared according to any of the above methods.
[0017] The present invention provides an application of a bimetal-MOF modified diaphragm in a lithium-sulfur battery.
[0018] The lithium-sulfur battery is assembled using a bimetallic-MOF modified diaphragm, comprising the following steps: (1) Lithium-sulfur battery positive electrode The sulfur and carbon black are mixed and ball-milled in a mass ratio of 7:3, and the ball-milled sulfur / carbon black is placed in a tube furnace under an inert atmosphere at 155° C. for 12 hours to obtain a sulfur / carbon black composite material; the sulfur / carbon black composite material is mixed with a binder in a mass ratio of 9:1 and N-methylpyrrolidone is added to obtain a slurry; the slurry is evenly coated on the surface of an aluminum foil, and vacuum dried at 60° C. to obtain a lithium-sulfur battery positive electrode; Alternatively, the sulfur / carbon black composite material, the conductive agent, and the binder are mixed in a mass ratio of 75:15:10, and then N-methylpyrrolidone is added and mixed evenly to obtain a uniform slurry; the slurry is coated on an aluminum foil, and vacuum dried at 60° C. to obtain a positive electrode sheet for a lithium-sulfur battery; (2) The positive electrode material was cut into thin sheets with a diameter of 12 mm to make a pole piece; metallic lithium was used as the counter electrode, and a CR2032 button cell was made in a glove box filled with argon gas. The bimetallic-MIL-101 modified separator was used, and the electrolyte was 1.0 mol·L -1 The lithium bis(trifluoromethylsulfonyl)imide is dissolved in a mixed solution of 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, and the additive is anhydrous lithium nitrate with a mass fraction of 1-2wt%.
[0019] The present invention takes lithium-sulfur battery separator as the research object, and modifies the surface of commercial battery separator with a layer of bimetallic-MIL-101 series material, wherein the metal cation has a strong catalytic effect on polysulfide conversion, inhibits the dissolution of polysulfide, slows down the shuttle effect, and improves the electrochemical performance of lithium-sulfur battery. When the modified separator is used in lithium-sulfur battery, it shows excellent cycle performance and rate performance. And its preparation method is simple, low-cost, environmentally friendly, and has a good prospect for industrial application.
[0020] The invention provides a modified diaphragm for lithium-sulfur batteries which can effectively inhibit polysulfide shuttling and a preparation method thereof, so as to improve the rate performance and cycle stability of lithium-sulfur batteries; and the preparation method thereof is simple to operate, low in cost, and suitable for industrial production.
[0021] The effective gain of the present invention is: The present invention coats the bimetallic-MIL-101 series material on the surface of the diaphragm. When the modified diaphragm is used in a lithium-sulfur battery, the dissolution of polysulfides is effectively reduced, and the shuttle effect is greatly suppressed. In addition, the bimetallic-MIL-101 has good lithium ion conductivity and acts as a current collector, which is conducive to the rapid conduction of electrons. The coating can still show good conductivity without adding any conductive agent, which greatly optimizes the electrochemical performance of the lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a charge and discharge curve diagram of Example 1; Figure 2 It is the rate performance diagram of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0024] Example 1 A bimetallic-MOF modified diaphragm for lithium-sulfur battery: prepared according to the following steps: S1. Add 0.5 mg of bimetallic-MIL-101 series metal organic framework material MIL-101 (Ti-Ni) into 10 mL of NMP to obtain a MIL-101 (Ti-Ni) mixed solution; S2, adding 0.25 mg of binder PVDF into 10 mL of NMP and mixing evenly to obtain a PVDF mixed solution; S3. Evenly mix the mixed solution of S1 and S2, and use the obtained mixed solution as a coating slurry, evenly apply it on the diaphragm body, and dry it naturally to obtain a MIL-101 (Ti-Ni) modified diaphragm with a coating layer thickness of 6 um.
[0025] Assembling lithium-sulfur batteries using MIL-101 (Ti-Ni) modified diaphragms: (1) Lithium-sulfur battery positive electrode The sulfur and carbon black are mixed and ball-milled in a mass ratio of 7:3, and the ball-milled sulfur / carbon black is placed in a tubular furnace under a nitrogen atmosphere at 155° C. for 12 hours to obtain a sulfur / carbon black composite material; the sulfur / carbon black composite material is mixed with a binder in a mass ratio of 9:1 and N-methylpyrrolidone is added to obtain a coating slurry; the slurry is evenly coated on the surface of an aluminum foil, and vacuum dried at 60° C. to obtain a lithium-sulfur battery positive electrode; (2) The positive electrode material was cut into thin sheets with a diameter of 12 mm to make a pole piece; metallic lithium was used as the counter electrode, and a CR2032 button cell was made in a glove box filled with argon. The bimetallic-MIL-101 modified diaphragm was used, and the electrolyte was a mixture of 1.0 mol·L-1 lithium bis(trifluoromethylsulfonyl)imide dissolved in a 1:1 volume ratio of 1,3-dioxolane and ethylene glycol dimethyl ether, and the additive was anhydrous lithium nitrate with a mass fraction of 1 wt%.
[0026] The charge and discharge performance of the samples was tested using the LandCT2001A battery test system, and the charge and discharge termination voltage was 1.5-2.8 V. The cyclic voltammetry test was performed using the Shanghai Chenhua CHI760E electrochemical workstation, with a scan rate of 0.1 mV·s-1 and a voltage range of 1.5-2.8 V.
[0027] Example 2 A bimetallic-MOF modified diaphragm for a lithium-sulfur battery is prepared by replacing the MIL-101 (Ti-Ni) in Example 1S1 with bimetallic-MIL-101 (Ti-Al), and the rest is the same as Example 1, according to the following steps: S1. Add 0.5 mg of bimetallic-MIL-101 series metal organic framework material MIL-101 (Ti-Al) into 10 mL of NMP to obtain a MIL-101 (Ti-Ni) mixed solution; S2, adding 0.25 mg of binder PVDF into 10 mL of NMP and mixing evenly to obtain a PVDF mixed solution; S3. Evenly mix the mixed solution of S1 and S2, and use the obtained mixed solution as a coating slurry, evenly apply it on the diaphragm body, and dry it naturally to obtain a MIL-101 (Ti-Al) modified diaphragm.
[0028] Lithium-sulfur batteries were assembled using MIL-101 (Ti-Al) modified separators.
[0029] Example 3 A bimetallic-MOF modified diaphragm for a lithium-sulfur battery is prepared by replacing the MIL-101 (Ti-Ni) in Example 1S1 with bimetallic-MIL-101 (Ti-Co), and the other parts are the same as those in Example 1, according to the following steps: S1. Add 0.5 mg of bimetallic-MIL-101 series metal organic framework material MIL-101 (Ti-Ni) into 10 mL of NMP to obtain a MIL-101 (Ti-Ni) mixed solution; S2, adding 0.25 mg of binder PVDF into 10 mL of NMP and mixing evenly to obtain a PVDF mixed solution; S3. Evenly mix the mixed solution of S1 and S2, and use the obtained mixed solution as coating slurry, evenly apply it on the diaphragm body, and dry it naturally to obtain the MIL-101 (Ti-Co) modified diaphragm.
[0030] Lithium-sulfur batteries were assembled using MIL-101 (Ti-Co) modified separators.
[0031] Comparative Example 1 A modified diaphragm is prepared by replacing MIL-101 (Ti-Ni) in S1 of Example 1 with MIL-101, and the other parts are the same as those of Example 1, thereby obtaining a MIL-101 modified diaphragm.
[0032] Lithium-sulfur batteries were assembled using MIL-101 modified separators.
[0033] Results and Analysis As shown in Table 1, the lithium-sulfur ion battery assembled with the bimetallic MIL-101 modified diaphragm obtained in the present invention exhibits good electrochemical performance, wherein the lithium-sulfur battery assembled with the MIL-101 (Ti-Ni) modified diaphragm obtained in Example 1 has a first discharge specific capacity of 1279.8 mAh g-1 and a first coulombic efficiency of 83.3%; while the lithium-sulfur battery assembled with the MIL-101 modified diaphragm obtained in Comparative Example 1 has a first discharge specific capacity of 1011.3 mAh g-1 and a first coulombic efficiency of 80.2%.
[0034] Figure 1 This is the charge and discharge curve of Example 1. It can be seen from the figure that the ΔE between the charge and discharge platforms of the lithium-sulfur battery prepared with MIL-101 (Ti-Ni) modified diaphragm is 363mV, indicating that the lithium-sulfur battery prepared with MIL-101 (Ti-Ni) modified diaphragm has a lower electrode polarization rate, which makes it have a smaller kinetic reaction barrier and higher reversibility.
[0035] Figure 2This is a comparison chart of the rate performance of Example 1 and Comparative Example 1. The 0.1C specific capacity is 1279.8 mAh g-1, the 20C specific capacity is 907.4 mAh g-1, and the 0.1C specific capacity is 1206.7 mAh g-1, showing excellent rate performance, indicating that the MIL-101 (Ti-Ni) modified diaphragm has good ability to inhibit the shuttle effect and improve the rate performance.
[0036] From the above analysis, it can be seen that the MIL-101 (Ti-Ni) modified diaphragm of the technical solution of the present invention blocks the diffusion of lithium polysulfide to the negative electrode without affecting the transmission of lithium ions, thereby inhibiting the shuttle effect of lithium-sulfur batteries, and the catalytic properties of Ti-Ni ions promote the conversion of polysulfides. The lithium-sulfur specific capacity and cycle stability prepared by it are greatly improved. This experiment has opened up a new path for the development of high-performance lithium-sulfur batteries and provided new inspiration for the evaluation protocol of the interface chemistry of lithium-S batteries. The method is simple, low-cost, and environmentally friendly, and has a good prospect for industrial application.
Claims
1. A method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery, characterized in that: include: S1, adding bimetallic-MIL-101 series metal organic framework materials into N-methylpyrrolidone (NMP) to obtain a mixed solution; S2, adding the binder into NMP and mixing evenly to obtain a mixed solution; S3, S1 and S2 are mixed evenly in a fixed ratio, and the obtained mixed solution is used as a coating slurry, and then the coating slurry is evenly coated on the surface of the battery diaphragm, and fully dried to obtain a bimetallic-MIL-101 modified diaphragm.
2. The method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery according to claim 1, characterized in that: The bimetallic-MIL-101 series metal organic framework materials are one or more of MIL-101 (Ti-Al), MIL-101 (Ti-Ni), MIL-101 (Ti-Co), MIL-101 and the like.
3. The method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery according to claim 1, characterized in that: In S3, the diaphragm is a PP diaphragm including Celgard2400 or a PE diaphragm.
4. The method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery according to claim 1, characterized in that: In S3, the drying is vacuum drying at 60° C. for 12 hours, or natural air drying.
5. The method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery according to claims 1 to 4, characterized in that: Prepare as follows: S1. Add 0.5 mg of bimetallic-MIL-101 series metal organic framework material MIL-101 (Ti-Ni) into 10 mL of NMP to obtain a MIL-101 (Ti-Ni) mixed solution; S2, adding 0.25 mg of binder PVDF into 10 mL of NMP and mixing evenly to obtain a PVDF mixed solution; S3. Evenly mix the mixed solution of S1 and S2, and use the obtained mixed solution as a coating slurry, evenly apply it on the diaphragm body, and dry it naturally to obtain a MIL-101 (Ti-Ni) modified diaphragm.
6. The method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery according to claims 1 to 4, characterized in that: Prepare as follows: S1. Add 0.5 mg of bimetallic-MIL-101 series metal organic framework material MIL-101 (Ti-Al) into 10 mL of NMP to obtain a MIL-101 (Ti-Ni) mixed solution; S2, adding 0.25 mg of binder PVDF into 10 mL of NMP and mixing evenly to obtain a PVDF mixed solution; S3. Evenly mix the mixed solution of S1 and S2, and use the obtained mixed solution as a coating slurry, evenly apply it on the diaphragm body, and dry it naturally to obtain a MIL-101 (Ti-Al) modified diaphragm.
7. The method for preparing a bimetallic-MOF modified diaphragm for a lithium-sulfur battery according to claims 1 to 4, characterized in that: Prepare as follows: S1. Add 0.5 mg of bimetallic-MIL-101 series metal organic framework material MIL-101 (Ti-Ni) into 10 mL of NMP to obtain a MIL-101 (Ti-Ni) mixed solution; S2, adding 0.25 mg of binder PVDF into 10 mL of NMP and mixing evenly to obtain a PVDF mixed solution; S3. Evenly mix the mixed solution of S1 and S2, and use the obtained mixed solution as a coating slurry, evenly apply it on the diaphragm body, and dry it naturally to obtain a MIL-101 (Ti-Co) modified diaphragm with a coating layer thickness of 6 um.
8. A bimetallic-MOF modified diaphragm for lithium-sulfur battery, characterized in that Prepared according to any one of claims 1 to 7.
9. Use of the bimetallic-MOF modified diaphragm according to claim 8 in a lithium-sulfur battery.
10. The use according to claim 9, characterized in that: The lithium-sulfur battery is assembled using a bimetallic-MOF modified diaphragm, comprising the following steps: (1) Lithium-sulfur battery positive electrode The sulfur and carbon black are mixed and ball-milled in a mass ratio of 7:3, and the ball-milled sulfur / carbon black is placed in a tube furnace under an inert atmosphere at 155° C. for 12 hours to obtain a sulfur / carbon black composite material; the sulfur / carbon black composite material is mixed with a binder in a mass ratio of 9:1 and N-methylpyrrolidone is added to obtain a slurry; the slurry is evenly coated on the surface of an aluminum foil, and vacuum dried at 60° C. to obtain a lithium-sulfur battery positive electrode; Alternatively, the sulfur / carbon black composite material, the conductive agent, and the binder are mixed in a mass ratio of 75:15:10, and then N-methylpyrrolidone is added and mixed evenly to obtain a uniform slurry; the slurry is coated on an aluminum foil, and vacuum dried at 60° C. to obtain a positive electrode sheet for a lithium-sulfur battery; (2) The positive electrode material was cut into thin sheets with a diameter of 12 mm to make the electrode piece; metallic lithium was used as the counter electrode, and a CR2032 button battery was made in a glove box filled with argon gas. The bimetallic-MIL-101 modified diaphragm was used, and the electrolyte was 1.0 mol·L -1 The lithium bis(trifluoromethylsulfonyl)imide is dissolved in a mixed solution of 1,3-dioxolane and ethylene glycol dimethyl ether in a volume ratio of 1:1, and the additive is anhydrous lithium nitrate with a mass fraction of 1-2wt%.